Strategic Foresight in the Federal Government: A Survey of Methods, Resources, and Institutional Arrangements. (September 2019) - Greenblott, Joseph M.; O'Farrell, Thomas; Olson, Robert; Burchard, Beth
The goal of this study is to help identify approaches and practices for improving Federal foresight efforts and the means for integrating foresight work into strategic planning and decision making. We present the results of semistructured interviews with people involved with foresight in 19 Federal agencies, and with two non-Federal experts on foresight in government. We discuss where agencies use similar approaches and where their approaches diverge, and include particularly insightful quotes from interviewees. We also discuss "broader observations" regarding the state of strategic foresight efforts across the Federal government and how our findings relate to opportunities and challenges to institutionalizing foresight in the Federal government.